Seasonal dynamics of geogenic phosphorus in alluvial-lacustrine aquifers: Coupling of phosphorus-containing dissolved organic matter and microbes as a key driver - Junna Ning; Yao Du; Baisong Deng; Mengze Li; Tianming Wu; Lijie Lin; Taiping Yu; Yiqun Gan; Dandan Si; Wen Zhang; Yanxin Wang (Water Research, 2027)

Cyprosulfamide effectively alleviates flusulfinam phytotoxicity in maize with enhanced dissipation - Yu Wang; Junqi Zhu; Mingdong Deng; Huijin Lin; Huanyu Zhou; Wenyu Dai; Ya Zhou; Tengfei Zhang; Yanmei Liu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Engineering a uridine diphosphate galactosyltransferase PhUGT enables efficient whole-cell biosynthesis of hyperoside from quercetin - Mengjiao Li; Zhiwei Deng; Yu Geng; Lu Cai; Shan Lin; Yue Gao; Yijian Rao (Food Bioscience, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Cascade delivery and synergistic ferroptosis-apoptosis induction via hybrid-membrane-coated MOF nanoparticles for glioblastoma therapy - Yue Huang; Zesheng Sun; Guiping Jiang; Qianqian Liu; Jialiang Lin; Song Deng; Yan Song; Yu Yang; Yinhao Chen; Yi Wang; Rongqin Huang; Jinlong Shi (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Platform-scale variability of Aeronian (early Silurian) δ13Ccarb excursions in the South China Block and its implications - Shenyang Yu; Zhongyang Chen; Stephen Kershaw; Lin Na; Shouxiang Wang; Shasha Liu; Yutao Wang; Yao Wang; Yingyan Mao; Xiaojie Deng; Qijian Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

The impact of low ambient pressure on the cavitation erosion intensity of aluminum alloy materials - Jian-Bo Li; Yong Xia; Wei-Lin Xu; Jun Deng; Jun Chen; Zhen-Yu Du (Ocean Engineering, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Performance enhancement in proton exchange membrane water electrolyzers through the metal foam flow fields with orderly arranged pore structure - Li Zhan; Shihao Lin; Qihao Deng; Wenshang Chen; Yi Yu; Guangfu Li; Ben Chen (Fuel, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

The role of exogenous electron donors in steering microbial electrosynthesis of multi-carbon fatty acids from carbon dioxide - Chenjia Miao; Xiaoman He; Chen Deng; Bing Song; Alec Foster; Yang Yu; Dekui Shen; Richen Lin (Bioresource Technology, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Non-Equilibrium Recovery of Plankton Communities in the Yangtze River Estuary: Three Years After the Fishing Ban - Bangping Deng; Wei Liu; Qiliang Song; Yuchen Guo; Chenxing Yang; Lin Zhu; Jun Li; Lijia Liu; Yin Yang; Xiucheng Yu (Fishes, 2026)
Large-scale fishing bans are increasingly implemented to restore aquatic ecosystems, yet their effects on lower trophic levels remain poorly understood. As one of the world’s largest estuarine systems, the Yangtze River Estuary has been subjected to a ten-year fishing ban since 2021, providing a unique opportunity to potentially examine the response of plankton community to reduced fishing pressure along a steep salinity–nutrient gradient. This study relies on one-off environmental and plankton field surveys conducted in autumn 2024 (a sampling instead of multi-year time-series monitoring), we applied redundancy analysis, Mantel tests, and threshold indicator taxa analysis to tentatively clarify the roles of nutrients and salinity in structuring post-ban plankton communities. Species richness may have increased substantially compared with pre-ban levels, but community evenness declined and the dominance of Skeletonema costatum could have intensified, revealing a possible non-equilibrium recovery pattern. Zooplankton density increased substantially, which may not be fully consistent with the expectation under a simple top-down release scenario. Threshold analysis showed that S. costatum exhibited bidirectional responses to dissolved inorganic nitrogen and phosphate, with its positive response thresholds matching ambient nutrient concentrations in the inner estuary; this discrepancy is only a plausible inference since we lack direct measurements of fish predation and zooplankton grazing rates to verify causal trophic interactions. Our findings suggest that bottom-up forces driven by persistent eutrophication remain the dominant control on plankton community structure three years after the ban. From a watershed management perspective, our observational results provide a tentative implication that substantial reductions in nutrient loading might be required to mitigate unbalanced plankton community recovery; otherwise, the structural integrity of plankton assemblages could lag far behind the recovery of species richness under the current eutrophic background.

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Sn-2 palmitate ameliorates dyslipidemia in high-fat-fed aged mice via bile acid-mediated gut-liver-adipose cross-talk - Lin Zhu; Mingzhe Deng; Hong Zhang; Zhenbo Xu; Peijin Tong; Jianchun Wan; Boyan Gao; Liangli (Lucy) Yu; Yaqiong Zhang (Food Bioscience, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Damage mechanism and optimization design of wall-type portal tunnels underseismic action: Seismic damage investigation and a theoretical model - Ming-Yu Chang; Deng Gao; Chao Wang; Hua Huang; Yi-lin Yu; Yusheng Shen (Soil Dynamics and Earthquake Engineering, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Effects of low-level lead exposure on hematological parameters and the possible underlying mechanisms - Xiaojing Liao; Tao Lin; Zhaorui Zhang; Peng He; Haimei Wu; Xinyi Ouyang; Qianxi Li; Zihan Yu; Ziyan Zhang; Jiahui Wu; Yingxin Guo; Shanshan Wang; et al. (Environmental Pollution, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Ammonium oxalate-mediated synergistic engineering of pores and defects in boron nitride granule catalysts for high-efficiency oxidative desulfurization - Tiantian Deng; Jing Lin; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2026)

Efficient lithium extraction from brines using a crown-like ether with multichannel binding mechanisms - Yi Deng; Yilun Sun; Kaiyong Wang; Bin Wang; Yu Lin; Guoliang Chai; Yinghe Zhang (Journal of Environmental Chemical Engineering, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Investigation of Microdamage and Seepage Evolution in Sandstone Under Coupled Thermomechanical Loading and Cooling Shocks via NMR - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Zhang; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2026)

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

Early Permian deltaic systems and weathering differentiation in the southwestern Yangtze Block, South China: Constraints from detrital zircon geochronology and paleogeography reconstruction - Xusheng Deng; Jintao Zhou; Wenchao Yu; Yuansheng Du; Shengyuan Ji; Ruiqin Lin (Journal of Asian Earth Sciences, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Degradation Pathways of Kraft Lignin by Novosphingobium sp. THN1: Insights into Refractory Dissolved Organic Matter Transformation in Lake Ecosystems - Chenyang Deng; Liwen Zhang; Chun Qing; Yuange Yu; Haorui Zhao; Genyi Wu; Yiqing Lin (Environmental Processes, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Variations in hydrochemical characteristics and their controlling factors among different types of lakes in the northeastern region of the Qinghai-Xizang Plateau - Jiping Chen; Ling Li; Weijie Li; Bingbing Liang; Yu Lin; Yutai Dai; Mengdi Zhao; Hong Shen; Xi Yang; Qiang Gao; Xuwei Deng (Environmental Monitoring and Assessment, 2026)

Anchoring Mechanism of Tunnel Free Face Subjected to Dynamic–Static Combined Load - Yu Chen; Zinuo Deng; Linchong Huang; Hang Lin; Yixian Wang; Yu Liang; Cungang Lin (Rock Mechanics and Rock Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

From hydrogeochemical genesis to public health risk: Unveiling the links between geogenic arsenic, fluoride, and iodine in groundwater - Furong Yu; Ao Li; Rui Li; Lin Wu; Deng Pan (Journal of Hazardous Materials, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Soil calcium ion enrichment associated with altered microbial functional gene networks in bamboo forest expansion - Yaoxing Wu; Huimin Tian; Jiahuan Guo; Yawen Shen; Qingqing Liu; Lin Yu; Zhiyin Tang; Yihang Jia; Gong Zhang; Jun Deng; Lianghua Qi (Applied Soil Ecology, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Ecological presence and functional role of bacteriophages in fermented vegetables - Xia Lin; Chunhui Deng; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Ziwei Liang; Lei Liu; Yu Rao (Food Microbiology, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Coupled regulation mechanisms of carbon sequestration, microbial communities, and manganese stabilization in manganese-contaminated soil by phosphorus-modified biochar - Yuyan Deng; Yu Yang; Lin Tu; Yifan Liao; Anyu Li; Huiquan Zhai; Hua Deng; Yang Li; Lening Hu (Applied Soil Ecology, 2026)

CT-HiffNet: A contour-texture hierarchical feature fusion network for cropland field parcel extraction from high-resolution remote sensing images - Hao Wu; Junyang Xie; Weihao Deng; Anqi Lin; Abdul Rashid Mohamed Shariff; Shamshodbek Akmalov; Wenbin Wu; Zhaoliang Li; Qiangyi Yu; Qunming Wang; Jian Zhang; Xin Mei; et al. (Computers and Electronics in Agriculture, 2025)

Failure mechanism of the critical safety distance between tunnels and karst caves subjected to multi-hole blasting dynamic load - Yu Chen; Jialong Deng; Linchong Huang; Hang Lin; Yixian Wang; Chenyang Zhao (Tunnelling and Underground Space Technology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Development of a three-directional isolation system for LNG storage tanks subjected to near-fault earthquakes - Jie-Ying Wu; Qian-Qian Yu; Xiang-Lin Gu; Tianhua Deng (Engineering Structures, 2025)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Luteolin modulates liver macrophage subtype polarization and play protective role in sepsis induced acute hepatic injury - Liangyong Deng; Qiulei Yu; Gang Kuang; Liuyang Wang; Jing Fan; Lin Ye (Inflammation Research, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Paleogene lithospheric evolution and gold-polymetallic mineralization in the western margin of South China block - Qingfei Wang; Yanning Wang; Chaoyi Dong; Lin Yang; Hesen Zhao; Huazhi Yu; Haoying Chen; Jun Deng (Science China Earth Sciences, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

A new exhalative sedimentary metallogenetic model for Permian manganese deposits in China - Zhichen Liu; Yu Liu; Sui Zhang; Lin Xiao; Jianxi Long; Deng Chen; Yang Wang; Zequan Wei; Yi Zheng; Liang Xiao (Journal of Asian Earth Sciences, 2025)

Simultaneous carrier concentration regulation and grain boundary passivation enable over 14 % efficient Ag-alloyed kesterite solar cells - Mengyang Wang; Yu Mao; Wenjian Chan; Yuanyuan Huang; Yanmei Deng; Ziyang Ren; Ening Gu; Xianzhong Lin; Guowei Yang (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Transcriptome analysis revealed that largemouth bass (Micropterus salmoides) may mobilize liver lipid metabolism to provide energy for adaptation to hypertonic stress - Xinxin Wang; Chaoyue Deng; Wenyan Lin; Huapeng Chen; Haoran Yu; Shukui Sun; Junlong Sun; Jian Luo; Feibiao Song (Aquaculture, 2025)

Microplastics impair black soldier fly bioconversion of pigeon manure: Physiological and transcriptomic insights - Zhimin Xu; Zheng Lin; Runtong Huang; Xueqing Chen; Lei Wang; Xingying Deng; Rui Du; Jiguang Gu; Yifan Wang; Renqiang Yu (International Biodeterioration & Biodegradation, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Dynamic effects of monopiles and sacrificial piles on Lagrangian residual velocity in an idealized rectangular bay - Xudong Liu; Cheng Fan; Lin Chen; Jinzhen Yu; Shuwen Zhang; Zhangliang Wei; Fangjing Deng (Ocean Engineering, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Corrigendum to “Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils” [Biomass & Bioenergy 197 (2025) 107823] - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Reprocessable bio-based rubber with hierarchical hydrogen bonding: A sustainable solution for high strength, superior extensibility, and recyclability - Wei-Chen Zhou; Xue-Qin Gao; Jia-Hao Li; Gui-Lin Hu; Yu-Zhong Wang; Cong Deng (Chemical Engineering Journal, 2025)

Revealing the Effect of Pore Size Distribution Characteristics on Macroscopic Properties of Red Sandstone Under Instantaneous High Temperature Through the Lens of Shannon Entropy Theory - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Yang Li; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2025)

Embracing Internal States: A Review of Optimization of Repetitive Transcranial Magnetic Stimulation for Treating Depression - Tingting Wu; Qiuxuan Yu; Ximei Zhu; Yinjiao Li; Mingyue Zhang; Jiahui Deng; Lin Lu (Neuroscience Bulletin, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Investigating the main contributors to esterification activity and identifying the aqueous-phase ester synthases in Daqu - Yu Tie; Lin Wang; Bo Ding; Zhao Deng; Qian Yang; Min Zhu; Zhengyun Wu; Lan Tang; Taikei Suyama; Wenxue Zhang (Food Bioscience, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Environmental Factors Influencing Groundwater Quality and Health Risks in Northern Henan Plain, China - Yu Ren; Wengeng Cao; Lihua Zhao; Shuai Wang; Deng Pan; Lin Zhang; Xiangzhi Li; Shunyu Xiao; Zeyan Li (Exposure and Health, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Association of early life co-exposure to ambient PM2.5 and O3 with the offspring's growth within two years of age: A birth cohort study - Yu Liu; Kunying Li; Yuchuan Deng; Mengfan Li; Xiaonan Gu; Yujing Chen; Zhaoyan Liu; Lizi Lin; Li Cai (International Journal of Hygiene and Environmental Health, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Blending of Sb2S3/PbS nanoparticles optimizes the CsPbI2Br perovskite/carbon electrode interface to facilitate efficient charge carrier transfer in perovskite solar cells - Fengli Liu; Haozhen Deng; Yu Jing; Lin Gao; Yuan Xu; Ruoshui Li; Chunyan Deng; Deng Wang; Zhenbo Du; Le Yang; Yicheng Cao; Jihuai Wu; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Biological activities of benzofurans from the fruits of Psoralea corylifolia L. and their mechanism based on network pharmacology and biological verification - Peixin Shi; Xiaohui Yu; Min Zhang; Lin Wang; Linkui Deng; Jun Yin; Na Han (Phytochemistry, 2025)

Rapid granulation of aerobic sludge for treatment of brewery wastewater: Aeration strategy and nitrogen removal mechanism - Songping Deng; Lidong Liu; Xiao-yan Li; Weiqi Xue; Jiajin Liang; Zehui Yu; Lin Lin (Journal of Environmental Chemical Engineering, 2025)

Effect of gibberellic acid treatment and cold stratification on breaking combined (physiological + mechanical) dormancy and germination in Sassafras tzumu (Hemsl.) Hemsl seeds - Yu Wu; Zhi Yun Deng; Ming Zhu Wang; Lin Yue Liu; Yong Bao Shen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

An efficient fungi-biochar-based system for advancing sustainable management of combined pollution - Ying Xia; Minghui Deng; Tao Zhang; Junjun Yu; Xinda Lin (Environmental Pollution, 2025)

Subduction-collision and rapid uplift of the NW Yangtze Block during the Ediacaran-Cambrian transition: new evidence from the shoshonite series - Qi Deng; Zheng-Jiang Wang; Hao Liu; Shuang-Jian Li; Jia-Hong Liu; Qi-Yu Wang; Jia-Shan Lin; Xiao-Wei Lan (International Geology Review, 2025)

Prospects of advanced oxidation processes for high-salinity coking wastewater treatment: A strategy to support sustainable management - Qili Peng; Jiangfang Yu; Ya Pang; Lifei Deng; Jing Tang; Jiajia Wang; Nile Wu; Lin Tang (Resources, Conservation and Recycling, 2025)

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

Low temperature-mediated changes in soil free-living nitrogen fixation functional groups in tree species at different successional stages in subtropical forests - Feng Sun; Wei Lin; Guangyan Deng; Linan Fan; Hanxia Yu; Zhengchao Yu; Changlian Peng (Plant and Soil, 2025)

Repurposing TAK-285 as An Antibacterial Agent against Multidrug-Resistant Staphylococcus aureus by Targeting Cell Membrane - Jinlian Huang; Zhichao Xu; Peikun He; Zhiwei Lin; Renhai Peng; Zhijian Yu; Peiyu Li; Qiwen Deng; Xiaoju Liu (Current Microbiology, 2025)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Chronology and geofluids characteristics of calcite cement in the Upper Triassic Xujiahe Formation tight sandstone reservoir, Western Sichuan Basin, SW China - Jianchao Zheng; Liangbiao Lin; Yu Yu; Qian Yuan; Long Wen; Xiang Deng; Yi Huang; Yuchao Qiu; Jiaqi Wei; Chao Zheng; Fanchi Nan (Marine and Petroleum Geology, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Fabrication of novel adsorptive photocatalyst GQDs/Sn3O4 for highly efficient synergistic removal of U(Ⅵ) - Yuting Deng; Jinchi Lin; Wentao Zhu; Jinhui Yang; Xiuming Yu; Zhui Tian; Shuibo Xie; Bin Yang (Journal of Environmental Chemical Engineering, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Deep dehumidification characteristics of a silica gel coated cross-flow heat exchanger with a circulating blowing loop - Lin Liu; Hongyu Huang; Jun Li; Yu Bai; Zhaohong He; Lisheng Deng; Tieyu Gao; Mitsuhiro Kubota; Noriyuki Kobayashi (Energy and Buildings, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

Enhanced mass scattering efficiencies of background dust aerosols over East Asia following the passage of dust plumes - Chenguang Tang; Yingjing Lin; Pengfei Tian; Jinsen Shi; Tao Deng; Xuejiao Deng; Yu Zou; Lei Zhang (Atmospheric Environment, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Dielectric screening modulating charge carrier recombination in high-performance of CsPbI2Br carbon-based perovskite solar cells - Fengli Liu; Yuan Xu; Ruoshui Li; Chunyan Deng; Lin Gao; Haozhen Deng; Yu Jing; Dongbin Jiang; Qing Yao; Chenfang Zhong; Deng Wang; Jihuai Wu; et al. (Chemical Engineering Journal, 2024)

Dual-mode immunochromatography based on Ti3C2Tx functionalized CdTe quantum dots for chloramphenicol detection in animal-derived foods - Mengfang Lin; Yu Wang; Mengyao Wang; Zehao Yang; Youwen Deng; Zhenlin Xu; Hongtao Lei; Xiangmei Li (Chemical Engineering Journal, 2024)

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

New insight into the contribution of Ca, Mn, and Mg component to vanadium extraction from vanadium slag - Tangxia Yu; Tao Jiang; Jing Wen; Dongsheng Deng; Lin Zhang; Yuepeng Li; Xiong Yang (Journal of Environmental Chemical Engineering, 2024)

Deep mineralization of bisphenol A via Cu–Mn spinel oxide nanospheres anchored N-doped carbon activated peroxymonosulfate - Xiaobo Wang; Lin He; Yu Zhou; Nan Wang; Lihua Zhu; JunTao Yan; Deng Ding; Wenjun Zhu; Xiaohua Zuo; Jinpeng Wang; Xiaoyong Wu (Chemical Engineering Journal, 2024)

Aflatoxins in dried chilli products in Gansu Province and health risk - Yongjun Li; Haiying Yu; Deng Liu; Shan Luo; Xiangna Gao; Lin Zhang; Jianyun Sun (Food Additives & Contaminants Part B-Surveillance, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

A distinct manganese deposit on a Middle Permian carbonate platform in South China - Wenchao Yu; Zhichen Liu; Bolin Zhang; Daoliang Chu; Wei Wei; Lin Xiao; Deng Chen; Yuansheng Du; Leslie J. Robbins; Kurt Konhauser (Chemical Geology, 2024)

Emergency room visits (ERVs) among occupational groups associated with ambient conditions in Taiwan - Ayushi Sharma; Kang Yajing; Min-Chun Lin; Liwen Deng; Yu-Kai Lin; Lin-Han Chianghsieh; Fung-Chang Sung; Yu-Chun Wang (International Archives of Occupational and Environmental Health, 2024)

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Machine learning-enabled high-throughput industry screening of edible oils - Peishan Deng; Xiaomin Lin; Zifan Yu; Yuanding Huang; Shijin Yuan; Xin Jiang; Meng Niu; Weng Kung Peng (Food Chemistry, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Molecular phylogenetic analysis of the East Asian hemicultrine fishes ( Teleostei: Cyprinidae: Xenocypridinae ), with suggestions to their generic classification and redescription of the recently described species Hemiculter yungaoi Vasil'eva et al. 2022 - Qiaoling Deng; Mingzheng Li; Dan Yu; Lin Chen; Wenjing Li; Xingwei Cai; Huanzhang Liu (Journal of Fish Biology, 2024)
The hemicultrine fishes are a group of small‐sized cyprinids, widely distributed but endemic to East Asian rivers and lakes. Till now, the taxonomic boundaries and relationships within this group remain poorly explored. In the present study, we study the phylogeny of this group, providing suggestions for classification of the hemicultrine group. Using two mitochondrial and three nuclear genes, and samples representing all genera, our results showed that the group consists of seven major lineages, of which four ( Hemiculterella , Hainania , Pseudolaubuca , and Anabarilius ) were monophyletic and three ( Hemiculter , Toxabramis , and Pseudohemiculter ) were not. Based on the phylogenetic tree, we redefined the genera. We revive the genus Siniichthys , which has three species, Siniichthys bleekeri , Siniichthys lucidus , and S. varpachovskii , that were previously treated as members of the genus Hemiculter but showed distant relationships to the genus Hemiculter in our phylogenetic tree. With the new results, a diagnostic key for clades of the hemicultrine group is provided. Furthermore, we provide more detailed information on diagnostic features of the recently described species Hemiculter yungaoi (Vasil'eva et al., 2022). This work will facilitate future systematic studies, pave the way for evolutionary studies, and provide valuable information for the urgent conservation of hemicultrine fishes.

High-resolution and real-time wastewater viral surveillance by Nanopore sequencing - Xiaoqing Xu; Yu Deng; Jiahui Ding; Qinling Tang; Yunqi Lin; Xiawan Zheng; Tong Zhang (Water Research, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

DPABINet: A toolbox for brain network and graph theoretical analyses - Chao-Gan Yan; Xin-Di Wang; Bin Lu; Zhao-Yu Deng; Qing-Lin Gao (Science Bulletin, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Microbial strategies for effective hexavalent chromium removal: A comprehensive review - Shilin Zha; Ao Yu; Zhongbing Wang; Qi Shi; Xunniu Cheng; Chunli Liu; Chunjian Deng; Guisheng Zeng; Shenglian Luo; Zongwen Zhao; Lin Zhou (Chemical Engineering Journal, 2024)

Ozone-delivering nanocomposite hydrogel for acute Staphylococcus aureus osteomyelitis treatment via neutrophil regulation - Hangtian Wu; Yihuang Lin; Yanpeng Lin; Mingye Deng; Jiahui Hou; Dahai Liu; Zhuang Cui; Daogang Guan; Jun Wang; Bin Yu (Chemical Engineering Journal, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Spatial distribution characteristics of carbazole and polyhalogenated carbazoles in water column and sediments in the open Western Pacific Ocean - Songtao Hu; Lijia Jiang; Lingbo Jiang; Leiming Tang; Anura Upasanta Kumara Wickrama Arachchige; Hao Yu; Zhaochao Deng; Longyu Li; Chunsheng Wang; Dongsheng Zhang; Chunlei Chen; Shiquan Lin; et al. (Journal of Hazardous Materials, 2024)

Mechanism of pore expansion and fracturing effect of high-temperature ScCO2 on shale - Chunsheng Yu; Hengchun Deng; Qi Jiang; Zhaoqi Fan; Xiang Zhou; Siyuan Huang; Qun Lin; Liangru Peng (Fuel, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Risk assessment and strontium isotopic tracing of potentially toxic metals in creek sediments around a uranium mine, China - Pengyuan Deng; Ke Lin; Wenhuan Yuan; Mario Alberto Gomez; Jingye She; Shan Yu; Mengqing Sun; Yanyi Liu; Jin Wang; Diyun Chen; Juan Liu (Chemosphere, 2024)

PdPtVO /CeO2−ZrO2: Highly efficient catalysts with good sulfur dioxide-poisoning reversibility for the oxidative removal of ethylbenzene - Jia Wang; Yuxi Liu; Jiguang Deng; Lin Jing; Xiuqing Hao; Xing Zhang; Xiaohui Yu; Hongxing Dai (Journal of Environmental Sciences, 2024)

Di-n-butyl phthalate promotes the neural differentiation of mouse embryonic stem cells through neurogenic differentiation 1 - Ying-Chu Lin; Kenly Wuputra; Kohsuke Kato; Chia-Chen Ku; Shigeo Saito; Michiya Noguchi; Yukio Nakamura; Michael Hsiao; Chang-Shen Lin; Deng-Chyang Wu; Atsushi Kawaguchi; Hsin-Su Yu; et al. (Environmental Pollution, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Seismic performance of prefabricated wall panels with sliding joints for reinforced concrete frames - Chao Zhang; Zijian Lin; Tianhao Yu; Weiyuan Huang; Xuesong Deng; Zexin Lin; Yuming Huang (Bulletin of Earthquake Engineering, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Environmental exposure disparities in ultrafine particles and PM2.5 by urbanicity and socio-demographics in New York state, 2013–2020 - Arshad Arjunan Nair; Shao Lin; Gan Luo; Ian Ryan; Quan Qi; Xinlei Deng; Fangqun Yu (Environmental Research, 2023)

Recalcitrant organic carbon plays a key role in soil carbon sequestration along a long-term vegetation succession on the Loess Plateau - Jingwei Shi; Mingyang Song; Lin Yang; Fei Zhao; Jianzhao Wu; Jiwei Li; Zhijing Yu; Ao Li; Zhouping Shangguan; Lei Deng (CATENA, 2023)

Soil C–N–P Stoichiometric Characteristics at the Aggregate Scales in Eucalyptus Plantations with Different Stand Types in Subtropical China - Yu Yan; Shengqiang Wang; Yuhong Cui; Chenyang Jiang; Jiazhen Deng; Mingye Lin; Shaoming Ye (Journal of Soil Science and Plant Nutrition, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Slab dehydration and potassium-lithium recycling in the forearc indicated by potassium and lithium isotope compositions of exhumed metabasites - Haiyang Liu; Tinggen Yang; Ying-Yu Xue; Jianghong Deng; Yilin Xiao; He Sun; Fengtai Tong; Kun Wang; Yongjun Gao; Kuan-Yu Lin; Fangyi Zhang; Xin Jin; et al. (Geochimica et Cosmochimica Acta, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

A review on takeaway packaging waste: Types, ecological impact, and disposal route - Yu Zhuo; JinTao He; Wen Li; Jing Deng; QinLu Lin (Environmental Pollution, 2023)

Dual application of Tribonema sp. GXU-A10 for purifying molasses vinasse and promoting the growth and health of Oreochromis niloticus - Hong-Yu Deng; Yue-Xin Sun; Xin-Qiang Chen; Yu Jiang; Wan-Lin Gu; Luo-Dong Huang; Pei-Hong Shen (Algal Research, 2023)

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

The SlARF4-SlHB8 regulatory module mediates leaf rolling in tomato - Xiaojuan Liu; Yuxiang Lin; Caiyu Wu; Yang Yang; Deding Su; Zhiqiang Xian; Yiyi Zhu; Canye Yu; Guojian Hu; Wei Deng; Zhengguo Li; Mondher Bouzayen; et al. (Plant Science, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

A zinc-octacarboxylate MOF with an unusual (6, 8)-connected ocu topology for high-capacity adsorptive separation of C8 alkylaromatics - Xiuping Deng; Maojun Deng; Yu-Lin Li; Zewei Liu; Tian-Fu Liu; Xin Chen; Shuhan Cai; Biying Liu; Jiesen Li; Daofei Lv; Jing Li; Wenbing Yuan (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

A strategy for regulation of gas–liquid microflow patterns by changing gas kinetic energy - Lin Sheng; Yu Chang; Junjie Wang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

Regulating catalytic stability of PtSnM/CeO2 (M = Mn, W, Nb) catalysts via the closely coupled multi-active sites to promote multicomponent VOCs oxidation - Ruyi Gao; Xinrong Tian; Xinlei Ding; Zhiquan Hou; Zeya Li; Xiaohui Yu; Jia Wang; Linke Wu; Lin Jing; Jiguang Deng; Yuxi Liu; Hongxing Dai (Chemical Engineering Journal, 2023)

Dietary administration of a postbiotic, heat-killed Pediococcus pentosaceus PP4012 enhances growth performance, immune response and modulates intestinal microbiota of white shrimp, Penaeus vannamei - Rolissa Ballantyne; Jai-Wei Lee; Sz-Tsan Wang; Jin-Seng Lin; Deng-Yu Tseng; Yi-Chu Liao; Hsiao-Tung Chang; Ting-Yu Lee; Chun-Hung Liu (Fish & Shellfish Immunology, 2023)

Hierarchical CoMn-LDH based photothermal membrane with low evaporation enthalpy and narrow bandgap toward highly efficient Solar-Driven evaporation - Ruoxuan Zheng; Tong Lin; Wan-Lei Zhao; Rutao Yin; Hongqiang Li; Zhuoqun Deng; Wei Chen; Yu-Fei Song (Chemical Engineering Journal, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

Engineering highly efficient NIR-II FRET platform for Background-Free homogeneous detection of SARS-CoV-2 neutralizing antibodies in whole blood - Lei Zhao; Qingwei Song; Weikang Mai; Min Deng; Yu Lei; Lu Chen; Weiya Kong; Lei Zhang; Lin Zhang; Yantao Li; Huiru Ye; Yiru Qin; et al. (Chemical Engineering Journal, 2023)

Conservation tillage increases surface soil organic carbon stock by altering fungal communities and enzyme activity - Wen-Sheng Liu; Yu-Xin Wei; Ping-Ping Deng; Olatunde Pelumi Oladele; Yves N’Dri Bohoussou; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2023)

Development and optimization of LED systems for surface fungal decontamination of fresh produce - Xinpeng Yu; Weihong Deng; Ziqian Zhang; Yuan Zou; Tao Wei; Junfang Lin; Liqiong Guo; Hyun-Gyun Yuk; Zhiwei Ye; Qianwang Zheng (Postharvest Biology and Technology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

The impact of temperature and precipitation on all-infectious-, bacterial-, and viral-diarrheal disease in Taiwan - Gerry Andhikaputra; Amir Sapkota; Yu-Kai Lin; Ta-Chien Chan; Chuansi Gao; Li-Wen Deng; Yu-Chun Wang (Science of The Total Environment, 2023)

Long-term exposure to particulate matter and COPD mortality: Insights from causal inference methods based on a large population cohort in southern China - Ying Wang; Zhicheng Du; Yuqin Zhang; Shirui Chen; Shao Lin; Philip K. Hopke; David Q. Rich; Kai Zhang; Xiaobo X. Romeiko; Xinlei Deng; Yanji Qu; Yu Liu; et al. (Science of The Total Environment, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Antibacterial activity and mechanism of action of bacteriocin LFX01 against Staphylococcus aureus and Escherichia coli and its application on pork model - Wei-Gang Xin; Gang Wu; Jian-Ping Ying; Yi-Zhou Xiang; Yu-Hang Jiang; Xian-Yu Deng; Lian-Bing Lin; Qi-Lin Zhang (Meat Science, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Hydrodynamics and mass transfer performance of gas–liquid microflow in viscous liquids - Lin Sheng; Yu Chang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Effects of cervicothoracic postures on the stiffness of trapezius muscles - Hongying Liang; Suiqing Yu; Man Hao; Weixin Deng; Ming Lin; Zheng Zhang; Chunlong Liu (Medical & Biological Engineering & Computing, 2022)

Toxicokinetics and metabolism of deoxynivalenol in animals and humans - Yu Sun; Jun Jiang; Peiqiang Mu; Ruqin Lin; Jikai Wen; Yiqun Deng (Archives of Toxicology, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Effects of soil organic matter components and iron aluminum oxides on aggregate stability during vegetation succession in granite red soil eroded areas - Zhe Lin; Zhi-gang Huang; Da-lan Liao; Wan-xia Huang; Juan Huang; Yu-song Deng (Journal of Mountain Science, 2022)

Transcriptome Changes Induced by Botrytis cinerea Stress and Weighted Gene Co-expression Network Analysis (WGCNA) in Actinidia chinensis - Zhe-Xin Li; Wen-Lin Zhang; Deng-Wei Jue; Xia Liu; Yu-Song Jiang; Jian-Min Tang (Plant Molecular Biology Reporter, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Mapping spatial-temporal nationwide soybean planting area in Argentina using Google Earth Engine - Yulin Shangguan; Xiyu Li; Yi Lin; Jinsong Deng; Le Yu (International Journal of Remote Sensing, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Ag3PO4-based photocatalysts and their application in organic-polluted wastewater treatment - Chunmu Yu; Xiaojuan Chen; Ning Li; Yue Zhang; Sailin Li; Jieming Chen; Liang Yao; Kaichun Lin; Yiqi Lai; Xinru Deng (Environmental Science and Pollution Research, 2022)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Stenotrophomonas strain CPCC 101271, an intestinal lifespan-prolonging bacterium for Caenorhabditis elegans that assists in host resistance to “Bacillus nematocida” colonization - Rui Han; Yu Wang; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)
The soil-dwelling, opportunistic pathogenic bacterium "Bacillus nematocida" B16 exhibits strong killing activities against a variety of pathogenic nematodes via a “Trojan horse” mechanism that can kill worm species like Caenorhabditis elegans . The bacterial strain CPCC 101271 was previously isolated from the intestines of C. elegans that were recovered from natural habitats and can serve as a probiotic for C. elegans , while also assisting in resistance to infection by the pathogenic strain B16. In this study, the lifespan of C. elegans fed with strain CPCC 101271 cells was extended by approximately 40% compared with that of worms fed with Escherichia coli OP50 cells. In addition, the colonization of C. elegans by the pathogenic bacterium "B. nematocida" B16 was inhibited when pre-fed with strain CPCC 101271. Metagenomic sequence analysis of intestinal microbiota of C. elegans fed with strain CPCC 101271 and infected with B16 revealed that pre-feeding worms with CPCC 101271 improved the diversity of the intestinal bacteria. Moreover, community structure significantly varied in coordination with Stenotrophomonas spp. and Bacillus spp. abundances when competition between strains CPCC 101271 and B16 was evaluated. In conclusion, the nematode microbiota strain CPCC 101271 assisted in its host resistance to colonization by the pathogen "Bacillus nematocida" and can also promote life span-prolongation in C. elegans. These results underscore that understanding the interactions between C. elegans microbiota and pathogens can provide new insights into achieving effective biological control of agricultural pests.

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Description of the reservoir along strike-slip fault zones in China T-Sh oilfield, Tarim Basin - Rui Zhao; Shang Deng; Lu Yun; Huixi Lin; Teng Zhao; Chen Yu; Qiangfu Kong; Qiang Wang; Huili Li (Carbonates and Evaporites, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Evaluation of the production-living-ecology space function suitability of Pingshan County in the Taihang mountainous area, China - Shu-hui Yu; Wei Deng; You-xin Xu; Xia Zhang; Hao-lin Xiang (Journal of Mountain Science, 2020)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

Effect of Freezing and Thawing on Microstructure Damage and Dynamic Flexural Tension of Granite - Chuanju Liu; JunRen Deng; Songtao Yu; Ping Li; Yun Lin (Rock Mechanics and Rock Engineering, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

An overview of COVID-19 - Yu Shi; Gang Wang; Xiao-peng Cai; Jing-wen Deng; Lin Zheng; Hai-hong Zhu; Min Zheng; Bo Yang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

A stochastic multi-objective optimization decision model for energy facility allocation: a case of liquefied petroleum gas station - Ming-Der Yang; Yi-Ping Chen; Chien-Tsung Wang; Ming-Jay Deng; Yu-Hao Lin; Ho-Wen Chen (Clean Technologies and Environmental Policy, 2020)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

An experimental study of the impacts of solar radiation and temperature on mercury emission from different natural soils across China - Han Xie; Maodian Liu; Yipeng He; Huiming Lin; Chenghao Yu; Chunyan Deng; Xuejun Wang (Environmental Monitoring and Assessment, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Quantitative trait locus mapping for panicle exsertion length in common wheat using two related recombinant inbred line populations - Yang Tao; Xin Yi; Yu Lin; Zhiqiang Wang; Fangkun Wu; Xiaojun Jiang; Shihang Liu; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; Youliang Zheng; et al. (Euphytica, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

The influences of industrial gross domestic product, urbanization rate, environmental investment, and coal consumption on industrial air pollutant emission in China - Wei-yu Zhou; Wen-lin Yang; Wen-xin Wan; Jing Zhang; Wei Zhou; Hao-shen Yang; Hua Yang; Hong Xiao; Shi-huai Deng; Fei Shen; Ying-jun Wang (Environmental and Ecological Statistics, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Variation in soil saturated hydraulic conductivity along the hillslope of collapsing granite gullies - Xiaoqian Duan; Yusong Deng; Yu Tao; Yangbo He; Lirong Lin; Jiazhou Chen (Hydrological Sciences Journal, 2018)

Gene locations may contribute to predicting gene regulatory relationships - Jun Meng; Wen-yuan Xu; Xiao Chen; Tao Lin; Xiao-yu Deng (Journal of Zhejiang University-SCIENCE B, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Environmental and cortisol-mediated control of Ca2+ uptake in tilapia (Oreochromis mossambicus) - Chia-Hao Lin; Wei-Chun Kuan; Bo-Kai Liao; Ang-Ni Deng; Deng-Yu Tseng; Pung-Pung Hwang (Journal of Comparative Physiology B, 2016)

GSTM1 Null Genotype and GSTP1 Ile105Val Polymorphism Are Associated with Alzheimer’s Disease: a Meta-Analysis - Mo Wang; Yu Li; Lulu Lin; Guijun Song; Teng Deng (Molecular Neurobiology, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Risk analysis and emergency actions for Hongshiyan barrier lake - Xingbo Zhou; Zuyu Chen; Shu Yu; Lin Wang; Gang Deng; Peijun Sha; Shouyi Li (Natural Hazards, 2015)

Structural transformation of oyster, hard clam, and sea urchin shells after calcination and their antibacterial activity against foodborne microorganisms - Yu-Chun Chen; Chun-Lan Lin; Chih-Ting Li; Deng-Fwu Hwang (Fisheries Science, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Brittle failure of shale under uniaxial compression - Yan Chuanliang; Deng Jingen; Hu Lianbo; Chen Zijian; Yan Xinjiang; Lin Hai; Tan Qiang; Yu Baohua (Arabian Journal of Geosciences, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

2.5D induced polarization forward modeling using the adaptive finite-element method - Yi-Xin Ye; Yu-Guo Li; Ju-Zhi Deng; Ze-Lin Li (Applied Geophysics, 2014)

Fosinopril improves the electrophysiological characteristics of left ventricular hypertrophic myocardium in spontaneously hypertensive rats - Zhi-Bin Huang; Chun-Yu Deng; Mao-Huan Lin; Gui-Yi Yuan; Wei Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

A new glutarimide derivative from marine sponge-derived Streptomyces anulatus S71 - Dandan Sun; Wei Sun; Yinxian Yu; Zhiyong Li; Zixin Deng; Shuangjun Lin (Natural Product Research, 2014)

Analytical Theory for One-Dimensional Consolidation of Soil Induced by Time-Dependent Pumping and Loading - Kang-He Xie; Da-Zhong Huang; Yu-Lin Wang; Yue-Bao Deng (Marine Georesources & Geotechnology, 2014)

The capability of estuarine sediments to remove nitrogen: implications for drinking water resource in Yangtze Estuary - Lin Liu; Dongqi Wang; Huanguang Deng; Yangjie Li; Siqi Chang; Zhanlei Wu; Lin Yu; Yujie Hu; Zhongjie Yu; Zhenlou Chen (Environmental Science and Pollution Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Pattern of benthic biomass size spectra from shallow waters in the East China Seas - Er Hua; Zhinan Zhang; Richard M. Warwick; Ke Deng; Kuixuan Lin; Ruizhao Wang; Zishan Yu (Marine Biology, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

The extremely high level expression of human serum albumin in the milk of transgenic mice - Xiaojie Wu; Yanli Lin; Fuyin Xiong; Yanrong Zhou; Fang Yu; Jixian Deng; Peitang Huang; Hongxing Chen (Transgenic Research, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of land cover changes induced by large physical disturbances on hydrological responses in Central Taiwan - Nien Ming Hong; Hone-Jay Chu; Yu-Pin Lin; Dung-Po Deng (Environmental Monitoring and Assessment, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)

Geostatistical approaches and optimal additional sampling schemes for spatial patterns and future sampling of bird diversity - Yu‐Pin Lin; Ming‐Sheng Yeh; Dong‐Po Deng; Yung‐Chieh Wang (Global Ecology and Biogeography, 2008)
Aim To evaluate geostatistical approaches, namely kriging, co‐kriging and geostatistical simulation, and to develop an optimal sampling design for mapping the spatial patterns of bird diversity, estimating their spatial autocorrelations and selecting additional samples of bird diversity in a 2450 km 2 basin. Location Taiwan. Methods Kriging, co‐kriging and simulated annealing are applied to estimate and simulate the spatial patterns of bird diversity. In addition, kriging and co‐kriging with a genetic algorithm are used to optimally select further samples to improve the kriging and co‐kriging estimations. The association between bird diversity and elevation, and bird diversity and land cover, is analysed with estimated and simulated maps. Results The Simpson index correlates spatially with the normalized difference vegetation index (NDVI) within the micro‐scale and the macro‐scale in the study basin, but the Shannon diversity index only correlates spatially with NDVI within the micro‐scale. Co‐kriging and simulated annealing simulation accurately simulate the statistical and spatial patterns of bird diversity. The mean estimated diversity and the simulated diversity increase with elevation and decrease with increasing urbanization. The proposed optimal sampling approach selects 43 additional sampling sites with a high spatial estimation variance in bird diversity. Main conclusions Small‐scale variations dominate the total spatial variation of the observed diversity due to a lack of spatial information and insufficient sampling. However, simulations of bird diversity consistently capture the sampling statistics and spatial patterns of the observed bird diversity. The data thus accumulated can be used to understand the spatial patterns of bird diversity associated with different types of land cover and elevation, and to optimize sample selection. Co‐kriging combined with a genetic algorithm yields additional optimal sampling sites, which can be used to augment existing sampling points in future studies of bird diversity.

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)